The cost of deep sleep: Environmental influences on sleep regulation are greater for diurnal lemurs. Issue 3 (10th July 2018) - Samson, David R.; Bray, Joel; Nunn, Charles L.
Abstract: Objectives: Primates spend almost half their lives asleep, yet we know little about how evolution has shaped variation in the duration or intensity of sleep (i.e., sleep regulation) across primate species. Our objective was to test hypotheses related to how sleeping site security influences sleep intensity in different lemur species. Methods: We used actigraphy and infrared videography to generate sleep measures in 100 individuals (males = 51, females = 49) of seven lemur species (genera: Eulemur, Lemur, Propithecus, and Varecia ) at the Duke Lemur Center in Durham, NC. We also generated experimental data using sleep deprivation for 16 individuals. This experiment used a pair‐wise design for two sets of paired lemurs from each genus, where the experimental pair experienced a sleep deprivation protocol while the control experienced normal sleeping conditions. We calculated a sleep depth composite metric from weighted z scores of three sleep intensity variables. Results: We found that, relative to cathemeral lemurs, diurnal Propithecus was characterized by the deepest sleep and exhibited the most disruptions to normal sleep‐wake regulation when sleep deprived. In contrast, Eulemur mongoz was characterized by significantly lighter sleep than Propithecus, and E. mongoz showed the fewest disruptions to normal sleep‐wake regulation when sleep deprived. Security of the sleeping site led to greater sleep depth, with access to outdoor housing linked to lighter sleep in all lemurs that were studied. Conclusions: We propose that sleeping site security was an essential component of sleep regulation throughout primate evolution. This work suggests that sleeping site security may have been an important factor associated with the evolution of sleep in early and later hominins.